(untitled) (Ocean and Coastal Research, 2022)
Femtoplankton and picophytoplankton organisms exert a major role in the balance between producers and consumers and are responsible for a large part of net primary production in the ocean. However, despite their ecological importance, the magnitude and drivers of their temporal dynamics remain largely unexplored. To address this significant knowledge gap, we performed weekly sampling over ten months in a wind-driven coastal upwelling area in the subtropical South Atlantic Ocean. We combined this intensive feldwork with multi-color fow cytometry and statistical modeling to investigate the temporal changes of both femto- and picophytoplankton at multiple temporal scales. We found that femtoplanktonic organisms (including virus-like particles) responded faster (i.e., without a temporal lag) to environmental changes, mainly related to chlorophyll-a (chl-a) and phaeopigment variations. On the other hand, picophytoplanktonic organisms showed a slower response to environmental changes, with positive responses to variation in pH and NH4 concentrations after a one-week lag. Overall, our results demonstrate that the speed of response of planktonic organisms to environmental changes may be dependent on their size, which highlights the importance of environmental variables and biological interactions as drivers of their temporal dynamics.